Temperature-dependent carbon isotope fractionation in coccolithophores - Torres-Romero, Ismael; Clark, Alexander J.; Wijker, Reto S.; Jaggi, Madalina; Zhang, Hongrui; Stoll, Heather M. (Frontiers in Earth Science, 2024)
The stable carbon isotope ratio of long-chain alkenones produced by marine haptophyte phytoplankton has often been used to estimate past variations in atmospheric CO2 throughout the Cenozoic. However, previous experimental studies and surveys of alkenones from surface sediment and suspended particulate matter document additional environmental and physiological influences on carbon isotopic fractionation in alkenones. To clarify the non-CO2 effects on the alkenone carbon isotope fractionations, an important alkenone producer, Gephyrocapsa oceanica, was cultured in laboratory. To separate effects of different environment parameters, G. oceanica was grown in continuous cultures under a matrix of environmental conditions in order to explore the influence of temperature independently of CO2(aq). Through careful manipulation of the media carbon system, we can control the variation of the media CO2(aq) independently of temperature solubility. Carbon isotope fractionations from alkenones, coccolith, and particulate organic carbon were measured from this steady state system. We find ep in alkenones and particulate organic carbon inversely correlates with temperature, and temperature affects ep more strongly than CO2(aq). The magnitude of the temperature effect can be explained by higher growth rates at warmer temperatures with a similar growth rate dependence as observed in previous cultures in which growth rate was regulated by other factors. Where the past temperature influence on growth rate could be constrained using the UK’37 alkenone index in the same samples, our finding offers an approach to deconvolve an important physiological factor affecting ancient alkenones ep, and may therefore improve past pCO2 estimates.